Local economic development strategies to increase economic growth in agrotourism areas - Mahanani, Retno Sari; Hidaya, Taufik; Wardati, Irma; Galushasti, Andarula; Wiyono, Luluk Cahyo (Turyzm/Tourism, 2021)
This study aims to find a local economic development strategy based on agroindustry to increase Java’s agrotourism sustainable and robust local economy. The research methods used are descriptive quantitative and qualitative. Research respondents are the community, academic practitioners and government officials. The data used covers both external and internal factors that affect the local economy in an agrotourism area and which are then analyzed using SWOT. The results show that the main strength of agrotourism in the IFE matrix is its highly strategic geographical location. The weakness is the lack of planning and business development activity which could have potential economic value. In the EFE matrix, opportunities are the prospects for agrotourism development while the main threat is the community's low interest in business development. In the IE matrix, agrotourism development is found in cell V. This can be handled by maintaining strategies such as market penetration, and market and product development. The study concludes that the local economic development of the community in the agrotourism area can be implemented if the community, practitioners and government are integrated to support the strategy.